2018
DOI: 10.1053/j.gastro.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Expression of STING Is Increased in Liver Tissues From Patients With NAFLD and Promotes Macrophage-Mediated Hepatic Inflammation and Fibrosis in Mice

Abstract: Levels of STING were increased in liver tissues from patients with NAFLD and mice with HFD-induced steatosis. In mice, loss of STING from macrophages decreased the severity of liver fibrosis and the inflammatory response. STING might be a therapeutic target for NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
328
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 286 publications
(342 citation statements)
references
References 45 publications
13
328
0
1
Order By: Relevance
“…For example, Tmem173 (also known as stimulator of interferon genes [STING]) expression was significantly increased in livers of mice with NASH as compared with mice with isolated steatosis in our study (Figure D), promoting us to hypothesize that targeting STING might be a good way to prevent NASH progression. Consistently, three studies published very recently provided various evidence to prove that activation of STING pathway contributes to liver inflammation and the progression of NASH . In addition, we observed that the mRNA of stearoyl‐CoA desaturases 1 ( Scd1 ) was significantly higher in mice with NASH (Figure D), which was consistent with the previous study that overexpression of SCD aggregated while pharmacological inhibitors of SCD attenuated liver fibrosis .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For example, Tmem173 (also known as stimulator of interferon genes [STING]) expression was significantly increased in livers of mice with NASH as compared with mice with isolated steatosis in our study (Figure D), promoting us to hypothesize that targeting STING might be a good way to prevent NASH progression. Consistently, three studies published very recently provided various evidence to prove that activation of STING pathway contributes to liver inflammation and the progression of NASH . In addition, we observed that the mRNA of stearoyl‐CoA desaturases 1 ( Scd1 ) was significantly higher in mice with NASH (Figure D), which was consistent with the previous study that overexpression of SCD aggregated while pharmacological inhibitors of SCD attenuated liver fibrosis .…”
Section: Discussionsupporting
confidence: 92%
“…Consistently, three studies published very recently provided various evidence to prove that activation of STING pathway contributes to liver inflammation and the progression of NASH. [32][33][34] In addition, we observed that the mRNA of stearoyl-CoA desaturases 1 (Scd1) was significantly higher in mice with NASH ( Figure 3D), which was consistent with the previous study that overexpression of SCD aggregated while pharmacological inhibitors of SCD attenuated liver fibrosis. 35 We have several more potential targets selected from the transcriptome results are being investigated currently.…”
Section: Bril F Et Al Revealed That Tg Accumulation In Livers Of Patisupporting
confidence: 91%
“…Total levels of STAT3 were elevated, but not in its activated phosphorylated form (pY705), which regulates gene transcription for modulation of immunosuppressive factors . The expression of STING suggests a macrophage‐mediated hepatic inflammation and fibrogenic process .…”
Section: Resultsmentioning
confidence: 99%
“…IRF3 can also be activated by stimulator of interferon genes (STING). However, activation of STING promotes both inflammation and injury . Interestingly, in other model systems, STING is both activated by endoplasmic reticulum (ER) stress and induces ER stress .…”
Section: Discussionmentioning
confidence: 99%
“…However, activation of STING promotes both inflammation and injury. (34) Interestingly, in other model systems, STING is both activated by endoplasmic reticulum (ER) stress (17) and induces ER stress. (35) This relation to ER stress may contribute to the proinflammatory effects of this pathway in HFD-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%